Success of Custommade Transobturator Slings Prepared From Conventional Polypropylene Mesh in the Treatment of Stress Urinary Incontinence in Women (Bangladesh Journal of Urology, 2020)
Objective: To observe the outcome of the transobturator tape, using custommade slings prepared from conventional polypropylene mesh in women in management of SUI.Materials and Methods: This prospective observational study was carried out from June 2010 to April 2015 among 35 patients who underwent the TOT procedure using handmade (polypropylene monofilament) slings; and complete at least the 12 month follow up period. Medical history, demographic characteristics, body mass indexes (BMI), menopausal status of patients, operation time, cost of sling, success of operation and complications were recorded. Before the operation, all patients were confirmed SUI through physical examination, urinalysis, urodynamic studies and ultrasonography. Placement of the sling to the midurethra was done in manner as described by Delorme. All the data were analyzed.Results: There were 35 patients with mean age 51.23 ± 5.63years, BMI 26.14 ± 3.70 kg/m². Twenty of the patients post were menopausal. The cost of the sling was 1200 BDT (15 USD). The success rate of TOT 12 months after surgery and at the last follow up was 91.5% and 88.6% respectively. Postoperative obstruction was noted in 2 patients, vaginal extrusion occurred in one case, de novo urgency and urinary tract infection (UTI) occurred in 2 patients. All of them were managed successfully with conservative treatments. There was no other early or late postoperative complication. There was significant improvement of the QoL and statistically no significant decrease in the Q max during the follow up period.Conclusion: Custommade mesh is a reasonable option in TOT surgery with good efficacy and cost effectiveness and complication like vaginal extrusion is also minimum.Bangladesh Journal of Urology, Vol. 18, No. 2, July 2015 p.49-55